Understanding the pressures of coaching: insights of young UK coaches working with elite junior tennis players - Gowling, C. (Coaching and Sport Science Review, 2019)
Despite a growing body of research into sports coaching there remains little understanding of what it is like to coach elite junior tennis players. The purpose of this study was to examine the lived coaching experience of 8 UK, less experienced tennis coaches and describe what it is like to be a coach of an elite junior tennis player. An Interpretative Phenomenological Analysis (IPA) of 8 less experienced tennis coaches (1 - 4 years-experience) provides a description of how they described elite junior tennis coaching. This study found that (a) self-employment makes coaching competitive, (b) less experienced coaches were surprised by the nature of parental interactions, and (c) less experienced coaches struggled to cope with the reality of coaching and this triggered disillusionment with coaching. The findings of this research contribute to an evolving, problematic epistemology of sports coaching and highlight a need for tennis coach education to improve the preparation of new coaches for their initiation into coaching. The findings present governing bodies opportunities to inform coach education literature and help tennis coaches to sustain themselves in an emotionally challenging role.